2007
DOI: 10.1111/j.1600-0463.2007.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous CD5+ marginal zone B‐cell lymphoma resembling the plasma cell variant of Castleman's disease

Abstract: Marginal zone B-cell lymphoma (MZBL) is occasionally associated with prominent plasma cell differentiation. However, MZBL rarely exhibits histological features that resemble plasmacytoma arising from a localized plasma cell variant of Castleman's disease (PCCD). We here report a histologically similar case that was associated with primary cutaneous tumor. The patient was a 57-year-old woman with a 5-year history of cutaneous nodules. Histologically, a prominent proliferation of plasma cells occupied the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Scattered cases of CD5+ MALT lymphoma have been reported in small numbers [2][3][4][5][6][7][8][9][10][11][12][13][14]. Some authors have suggested that CD5 expression is associated with an aggressive clinical course marked by widespread dissemination [2,9,11], but others have reported CD5 expression in localized, otherwise typical cases of MALT lymphoma [3,4,8,10,13].…”
Section: Introductionmentioning
confidence: 98%
“…Scattered cases of CD5+ MALT lymphoma have been reported in small numbers [2][3][4][5][6][7][8][9][10][11][12][13][14]. Some authors have suggested that CD5 expression is associated with an aggressive clinical course marked by widespread dissemination [2,9,11], but others have reported CD5 expression in localized, otherwise typical cases of MALT lymphoma [3,4,8,10,13].…”
Section: Introductionmentioning
confidence: 98%
“…B cells are known to be characterized by CD5 expression in the expanded mantle zones of CD. In contrast, CD5 positivity is unusual in MALT lymphomas except for some rare cases [32], that can even closely mimic CD [33]. For establishing the accurate diagnosis, careful histopathologic examinations are needed, immunohistological examinations and immunologic gene rearrangement analysis can be helpful in the differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Kubota et al [9] reported 3 case of CD5-positive MALT lymphoma of orbit with autoantibodies. Tsukamoto et al [10] reported a case of cutaneous CD5-positive MALT lymphoma resembling the plasma cell variant of Castleman's disease. Wenzel et al [11] reported a case of CD5-positive MALT lymphoma of the conjunctiva with early dissemination and aggressive clinical behavior.…”
Section: Discussionmentioning
confidence: 99%